2006
DOI: 10.1007/s00125-006-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

The relation between size at birth and risk of type 1 diabetes is not influenced by adjustment for the insulin gene (-23HphI) polymorphism or HLA-DQ genotype

Abstract: Aims/hypothesis: Associations have been described between higher birthweight and increased risk of type 1 diabetes, and of insulin (INS) and human leucocyte antigen (HLA) genotypes that protect against diabetes with larger size at birth. We studied simultaneously the effects of size at birth, INS and HLA genotypes on the risk of type 1 diabetes to test whether the relation between size at birth and risk of type 1 diabetes would be strengthened after adjustment for INS and HLA genotypes. Subjects and methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
4
20
1
1
Order By: Relevance
“…It is also possible that some unknown genetic factor predisposes to high birthweight and increased risk of type 1 diabetes. Although one study [56] has demonstrated that established type 1 diabetes high-risk HLA genotypes are associated with higher birthweight in the general population, another [57], which recorded established HLA and insulin gene polymorphisms, demonstrated that the observed association between type 1 diabetes and birthweight was independent of these genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that some unknown genetic factor predisposes to high birthweight and increased risk of type 1 diabetes. Although one study [56] has demonstrated that established type 1 diabetes high-risk HLA genotypes are associated with higher birthweight in the general population, another [57], which recorded established HLA and insulin gene polymorphisms, demonstrated that the observed association between type 1 diabetes and birthweight was independent of these genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The INS VNTR type 1 diabetes susceptibility locus has been inconsistently reported to affect birthweight and growth during childhood [29,30,[33][34][35]. Homozygosity for INS VNTR class III alleles was associated with increased birthweight in a subgroup of children from south-west England who did not show 'catch-up' or 'catch-down' weight changes from birth to age 2 years [29].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity for INS VNTR class III alleles was associated with increased birthweight in a subgroup of children from south-west England who did not show 'catch-up' or 'catch-down' weight changes from birth to age 2 years [29]. The INS VNTR class III allele was associated with reduced birthweight in Pima Indians [30], whereas studies in much larger cohorts from England, Finland and Norway failed to find any association between INS VNTR genotypes and birthweight [33][34][35]. Similarly, an association between INS VNTR genotypes and weight in childhood and adulthood was also reported, but a more recent report failed to confirm the original findings [36].…”
Section: Discussionmentioning
confidence: 99%
“…11 It is not clear whether high (X4000 g) or low (p2500 g) birthweight (BW) increases the risk of T1D or whether no association exists between BW and T1D. [12][13][14][15][16][17] Findings from recent epidemiological studies suggest an association between high BW and an increased risk of T1D, especially in children with a BW of 4000 g or more. 14,15 It has also been shown that infants born large for gestational age have an increased risk of T1D.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, an inverse relationship between T1D susceptibility genotypes and BW has also been observed, 25 and a recent study reported no evidence for interaction between HLA and BW, although children with the non-susceptibility DQB1*0602 allele tended to be heavier at birth. 17 The aim of the study was to evaluate whether T1D-associated HLA haplotypes were associated with BW among Finnish families with a T1D offspring. The mean BWs of children in families with a T1D offspring and in the general population were compared.…”
Section: Introductionmentioning
confidence: 99%